PENGARUH KEMAMPUAN PENGELOLAAN KEUANGAN DAERAH DAN KOMITMEN ORGANISASI, TERHADAP PENYUSUNAN LAPORAN KEUANGAN DINAS PERHUBUNGAN PROVINSI BALI DENGAN SISTEM PENGENDALIAN INTERN SEBAGAI VARIABEL MODERASI - Made Dwi Kharisma Dewi; Ni Wayan Yuniasih (UNHI Press, 2020)
The main purpose of this study is to determine whether there is an influence of the ability ofregional financial management and organizational commitment to the preparation offinancial reports with an internal control system as a moderating at the TransportationService of the Province of Bali. Sampling using a purposive sampling technique, with apopulation of employees of the Transportation Department of the Province of Bali, andobtained a sample of 58 people. The questionnaire is the source of the data of this study,using moderation regression analysis as a data analysis technique showing the ability ofregional financial management to influence the preparation of the financial statements ofthe Bali Provincial Transportation Agency, the organizational commitment influences thepreparation of the Bali Provincial Transportation Department and organizationalcommitment to the preparation of financial reports in the Bali Provincial TransportationAgency.